Corporate Swine and Capitalist Pigs: A Decade of Environmental Injustice and Protest in North Carolina - Ladd, Anthony E. (Social justice, 2002)
Part of a special issue on global threats to security. The writers explore the growth of the controversy over swine production in North Carolina and the role that environmental justice concerns and grassroots protest played in its evolution thus far. They describe the explosive growth in swine and concentration of corporate pork production in North Carolina, which since the early 1990s has been the fastest growing swine producing state in the U.S. and the national innovator in industrialized pork production. They consider the implications of these recent developments in terms of how community concerns over corporate hog production are converging with wider environmental justice and anticorporate, sustainable agriculture movement objectives.